MIRAGRODEP, an analytical model adapted to economic and trade reforms - Bouët, Antoine; Laborde Debucquet, David; Piñeiro, Valeria (Instituto Interamericano de Cooperación para la Agricultura, 2021)
The international community is facing considerable challenges today. To meet these challenges, governments, regional bodies, and international institutions must define and implement reforms that meet a triple requirement: inclusiveness, sustainability and resilience. Inclusiveness means the implementation of reforms that primarily benefit the most disadvantaged populations in terms of income, food security, and/or health status. Sustainability means the design of solutions that favor the fight against climate change and the respect of biodiversity. Resilience means finding out tools that enable economies and populations to resist external shocks (extreme climatic events, pandemics).